Correlation Between English Learning Motivation and Daily Vocabulary Mastery of Grade VIII Students at SMP Negeri 5 Palu - Shiva Aulia; Mochtar Marhum; Zarkiani Hasyim; Mawardin M. Said (Journal of General Education and Humanities, 2026)
Many junior high school students experience difficulty actively using English vocabulary in authentic communication, and their level of learning motivation may contribute to this difficulty. This study aimed to examine the correlation between English learning motivation and daily vocabulary mastery among eighth-grade students at SMP Negeri 5 Palu. A quantitative correlational research design was employed. The population consisted of 131 students, and 50 students were selected through simple random sampling. Data were collected using a 20-item Likert-scale questionnaire measuring intrinsic, extrinsic, integrative, and instrumental motivation, and a 20-item multiple-choice test assessing daily vocabulary mastery. The data were analyzed using descriptive statistics and Spearman’s rho correlation analysis due to non-normal data distribution. The results showed that students’ motivation was generally high (M = 77.04), and their daily vocabulary mastery was at a good level (M = 74.20). A very strong, statistically significant positive correlation was found between the two variables (r = 0.876, p < 0.01). These findings indicate that higher motivation is strongly associated with better daily vocabulary mastery.